Can we still do something-and what? - for a seemingly missing syndrome?: "Yes we can" - Raffaele Piumelli; Cinzia Arzilli; Niccolò Nassi; Marta Peruzzi; Carola-Maria Ernst; Cristina Salvatori (BMC, 2019)
Abstract In this letter, the authors compare the incidence of SUDI and SIDS in the Tuscany Region to the incidence reported by Campi and Bonati in their paper "Can we still do something-and what?- for a seemingly missing syndrome?" that was recently published in this journal. The Tuscany data are directly gathered from the autopsies while the others from the death certificates that are often not reilable, thus causing an understimation of the phenomenon. The real picture of the extent of SIDS is crucial to evaluate the effectiveness of back to sleep campaigns.